Transcutaneous measurement of glomerular filtration rate in small rodents: Through the skin for the win?. (March 2015) - Ellery, Stacey J; Cai, Xiaochu; Walker, David D; Dickinson, Hayley; Kett, Michelle M
Abstract Rodent models of renal physiology and pathology are crucial to our understanding of the molecular, histological and functional sequelae that contribute to kidney diseases. One of the most important measures of renal function is glomerular filtration rate (GFR). While the accurate determination of GFR is pivotal to understanding the progression of disease and/or the benefits of treatment strategies, in rodents the conventional methods for assessment of GFR are inconvenient and cumbersome, not the least because they involve stress and often anaesthesia. The legitimacy of assay‐based assessment of plasma and urine markers of GFR in mice has also been heavily scrutinized for their insensitivity to minor declines in GFR and inaccurate detection of renal biomarkers. While infusion‐based clearance methods of GFR assessment are thus the gold standard in terms of accuracy, they are limited by the fact that they are primarily non‐recovery procedures. This presents a dilemma when trying to document the progression of renal disease, as these measures cannot be taken in the same experimental subject. Here we review a technique of transcutaneous measurement of fluorescein isothiocyanate‐labelled sinistrin to calculate GFR in small rodents, using a non‐invasive clearance device (NIC‐Kidney Device). This is a recently validated non‐invasive technique for measuring GFR in small rodents that allows for the real‐time measurement of GFR in conscious animals, without the need for plasma and urine assays.